The policy space in international intellectual property law - Oke, Emmanuel Kolawole (Nijhoff international trade law series ;, 2022)
"This book presents a critical and original examination of the policy space in international intellectual property law through the unique lens of glocalisation. Distinguishing between the unregulated local space and the regulated glocal space as distinct components of this policy space, it contends that it is within the glocal space that states can resist or adapt the globalising waves flowing from the international intellectual property system. It discusses both the contours and the components of this glocal space. It further highlights the important role that the WTO's adjudicatory bodies play in preserving this glocal space in international intellectual property law"--